2009
DOI: 10.4314/ajfand.v9i4.43874
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological quality of sachet water produced and sold in Teshie-Nungua suburbs of Accra, Ghana

Abstract: Access to good quality drinking water is a challenge in most towns and cities in Ghana and households have for years depended on other sources of water to supplement their activities. The introduction of sachet water to consumers was to provide safe, hygienic and affordable instant drinking water to the public. Although this is a laudable idea, current trends seem to suggest that sachet drinking water could be a route of transmission of diseases. The objective of this study was to determine the bacteriological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 14 publications
4
46
1
Order By: Relevance
“…Also Addo et al (2009) in the study of bacteriological quality of sachet water produced and sold in Teshie-Nungua suburbs of Accra, Ghana detected faecal coliforms and Escherichia coli which were attributed to poor treatment and handling methods in some sachet water producing industries. The moderately high particles found on some sachet water could be as a result of poor filtration techniques that make the passage of these particles easy.…”
Section: Discussionmentioning
confidence: 99%
“…Also Addo et al (2009) in the study of bacteriological quality of sachet water produced and sold in Teshie-Nungua suburbs of Accra, Ghana detected faecal coliforms and Escherichia coli which were attributed to poor treatment and handling methods in some sachet water producing industries. The moderately high particles found on some sachet water could be as a result of poor filtration techniques that make the passage of these particles easy.…”
Section: Discussionmentioning
confidence: 99%
“…Water used for "pure water" is mostly obtained from ground water, springs and potable pipe-borne water. Prior to packaging, the water goes through a number of treatment processes, mainly filtration, in an attempt to make it purer and safer for consumption 3 . Most households and families depended greatly on tap water from the Ghana Water Company Limited (GWCL) for drinking and household activities including cooking 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In a study to investigate the bacteriological quality of sachet water produced and sold in Teshie-Nungua, a suburb known for perennial water shortages, Addo et al (2009) reported sachet water sampled with suspicious microbial contaminations based on the most probable number (MPN) values. Fecal coliforms were detected in several samples while some of the samples were also contaminated with Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
“…8 Those who do not have access to safe water, as well as those who have access but cannot afford, rely on other sources of water with questionable quality. 9 The microbiological quality of drinking water is a concern to consumers, water suppliers, regulators and public health authority alike. The potential of drinking water to transport microbial pathogens to great number of people, causing subsequent illness is well documented in countries at all levels of economic development.…”
Section: Introductionmentioning
confidence: 99%